Oxygen and hydroxyl adsorption on MS2 (M = Mo, W, Hf) monolayers: a first‐principles molecular dynamics study. Issue 11 (13th September 2016) - Iordanidou, K.; Houssa, M.; Pourtois, G.; Afanas'ev, V. V.; Stesmans, A.
Abstract : In this paper, we study the oxygen and hydroxyl adsorption on both pristine and S deficient MS2 (M = Mo, W, Hf) monolayers, using first‐principles molecular dynamics calculations. Our simulations reveal that single‐layer HfS2 suffers severely from oxidation, which results in the formation of strong Hf–O bonds, likely degrading the transport properties of the material. Oxygen adsorption on S deficient monolayers acts as a passivation mechanism, both "structurally" by saturating the dangling bonds of neighboring metal atoms and "electronically" by removing the S vacancy induced gap states. Hydroxyl adsorption on pristine monolayers generates spin‐polarized gap states, and for HfS2 in particular, causes the Fermi level pinning close to the conduction band edge. Abstract : Oxygen and hydroxyl adsorption on MS2 (M = Mo, W, Hf) monolayers is studied through molecular dynamics simulations. Single layer HfS2 suffers severely from oxidation, leading to the increase of materials energy band gap and electron effective mass. The oxidation of S deficient monolayers acts as a passivation mechanism, both structurally and electronically.